3D printed hybrid scaffolds for bone regeneration using calcium methoxyethoxide as a calcium source - Heyraud, Agathe; Tallia, Francesca; Sory, David; Ting, Hung-Kai; Tchorzewska, Anna; Liu, Jingwen; Pilsworth, Hannah L.; Lee, Peter D.; Hanna, John V.; Rankin, Sara M.; Jones, Julian R. (Frontiers in Bioengineering and Biotechnology, 2023)
Hybrids consist of inorganic and organic co-networks that are indistinguishable above the nanoscale, which can lead to unprecedented combinations of properties, such as high toughness and controlled degradation. We present 3D printed bioactive hybrid scaffolds for bone regeneration, produced by incorporating calcium into our "Bouncy Bioglass", using calcium methoxyethoxide (CME) as the calcium precursor. SiO2-CaOCME/PTHF/PCL-diCOOH hybrid "inks" for additive manufacturing (Direct Ink Writing) were optimised for synergy of mechanical properties and open interconnected pore channels. Adding calcium improved printability. Changing calcium content (5, 10, 20, 30, and 40 mol.%) of the SiO2-CaOCME/PTHF/PCL-diCOOH hybrids affected printability and mechanical properties of the lattice-like scaffolds. Hybrids containing 30 mol.% calcium in the inorganic network (70S30CCME-CL) printed with 500 µm channels and 100 µm strut size achieved the highest strength (0.90 ± 0.23 MPa) and modulus of toughness (0.22 ± 0.04 MPa). These values were higher than Ca-free SiO2/PTHF/PCL-diCOOH hybrids (0.36 ± 0.14 strength and 0.06 ± 0.01MPa toughness modulus). Over a period of 90 days of immersion in simulated body fluid (SBF), the 70S30CCME-CL hybrids also kept a stable strain to failure (~30 %) and formed hydroxycarbonate apatite within three days. The extracts released by the 70S30CCME-CL hybrids in growth medium did not cause cytotoxic effects on human bone marrow stromal cells over 24 h of culture.